A PROPÓSITO DE LAS FUENTES CLÁSICAS DEL SONETO DE QUEVEDO: «SOLA EN TI, LESBIA,...» - Rodríguez Herrera, Gregorio (Myrtia, 1995)
The purpose of this paper is to demonstrate that Quevedo’s sonnet ’Sola en ti, Lesbia,...’, whose main source is Martial 1, 35 (34), may also have other indirect sources such as Ovid’s ’Amores’, 3, 4, and Cicero’s ’Pro Caelio’. These indirect sources could explain the expansions and deviations Quevedo’s sonnet presents with regard to Martial’s epigram.